The Garden Diary of Martha Turnbull, Mistress of Rosedown Plantation - Turnbull, Martha Barrow, 1809-1896 (Book collections on Project MUSE., 2012)
Recovered in the mid-1990s from the attic of a Turnbull family descendant, Martha Turnbull's garden diary offers the most extensive surviving first-hand account of nineteenth-century plantation life and gardening in the Deep South. Landscape architecture professor and preservationist Suzanne Turner spent fifteen years transcribing and annotating the original manuscript, making it accessible to twenty-first-century gardening enthusiasts. The resulting dialogue between Turnbull's diary entries and Turner's illuminating notes demonstrates the pivotal role that kitchen and pleasure gardens held in the lives of planter families. In addition, the diary documents the relationship between the mistress and the enslaved whose labor made her vast gardens possible. Turner's exquisite interpretation reveals not only an energetic gardener but also a well-read one, eager to experiment with the newest gardening trends. Illustrated with engravings from period books, journals, and nursery catalogs, Turner's annotations provide the reader with a deeper understanding of American horticultural history. The diary, spanning the years 1836 through 1894, reveals the portrait of a courageous and resilient woman. After the tragic loss of her two sons and husband prior to the Civil War, Martha assumed full responsibility for her family and the plantation. She endured living under siege during the war and persevered during Reconstruction by growing and selling food as a truck farmer. By working daily in her ornamental garden and faithfully maintaining her diary for nearly sixty years, she found the solace and peace to look forward to the future.